Cities of Medieval Iran
1 online resource.
Keywords: Cities of Medieval Iran brings together studies in urban geography, archaeology, and history of medieval Iranian cities, spanning the Islamic period until ca. 1500, but also the pre-Islamic situation. The cities and their inhabitants take centre stage, they are not just the places where something else happened. Urban actors are given priority over external factors. The contributions take a long-term perspective and thus take the interaction between urban centres and their hinterland into account. Many contributions come from history or archaeology, but new disciplines are also methodologically integrated into the study of medieval cities, such as the arts of the book, lexicography, geomorphology, and digital instruments. Contributors include Denise Aigle, Mehrdad Amanat, Jean Aubin, Richard W. Bulliet, Jamsheed K. Choksy, David Durand-Guédy, Etienne de la Vaissière, Majid Montazer Mahdi, Roy P. Mottahedeh, Jürgen Paul, Rocco Rante, Sarah Savant, Ali Shojai Esfahani, Donald Whitcomb and Daniel Zakrzewski.